An Experimental Study of Combustion of a Methane Hydrate Layer Using Thermal Imaging and Particle Tracking Velocimetry Methods - Misyura S. Y.; Voytkov I. S.; Morozov V. S.; Manakov A. Y.; Yashutina O. S.; Ildyakov A. V. (Energies, 2018)
In this paper, the combustion of methane hydrate over a powder layer is experimentally studied using thermal imaging and Particle Tracking Velocimetry (PTV) methods. The experiments are carried out at different velocities of the external laminar air-flow from zero to 0.6 m/s. Usually, simulation of methane hydrate combustion is carried out without taking into account free convection. A standard laminar boundary layer is often considered for simplification, and the temperature measurements are carried out only on the axis of the powder tank. Measurements of the powder temperature field have shown that there is a highly uneven temperature field on the layer surface, and inside the layer the transverse temperature profiles are nonlinear. The maximum temperature always corresponds to the powder near the side-walls, which is more than 10 °C higher than the average volumetric temperature in the layer. Thermal imager measurements have shown the inhomogeneous nature of combustion over the powder surface and the highly variable velocity of methane above the surface layer. The novelty of the research follows from the measurement of the velocity field using the PTV method and the measurement of methane velocity, which show that the nature of velocity at combustion is determined by the gas buoyancy rather than by the forced convection. The maximum gas velocity in the combustion region exceeds 3 m/s, and the excess of the oxidizer over the fuel leads to more than tenfold violation of the stoichiometric ratio. Despite that, the velocity profile in the combustion region is formed mainly due to free convection, it is also necessary to take into account the external flow of the forced gas U0. Even at low velocities U0, the velocity direction lines significantly deviate under the forced air-flow.